2015
DOI: 10.1111/ijs.12520
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arterial Bone Marrow Mononuclear Cells (BM-MNCS) Transplantation in Acute Ischemic Stroke (IBiS Trial): Protocol of a Phase II, Randomized, Dose-Finding, Controlled Multicenter Trial

Abstract: This is the first trial to explore efficacy of different doses of intra-arterial bone marrow mononuclear cell in moderate-to-severe acute ischemic stroke patients. The trial is registered as NCT02178657.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…The results suggest that this therapy is feasible and seems to be safe. A phase II, randomized, dose-finding, controlled multicenter trial on intra-arterial bone marrow cells transplantation in patients with acute ischemic stroke (IBIS trial) has been launched recently 319 .…”
Section: Application Of Vascular Precursor Cells In the Treatment Of mentioning
confidence: 99%
“…The results suggest that this therapy is feasible and seems to be safe. A phase II, randomized, dose-finding, controlled multicenter trial on intra-arterial bone marrow cells transplantation in patients with acute ischemic stroke (IBIS trial) has been launched recently 319 .…”
Section: Application Of Vascular Precursor Cells In the Treatment Of mentioning
confidence: 99%
“…In preclinical studies, no relevancy was reported for dose dependent functional outcome in NSCs therapy, but some clinical trials reported a better functional outcome correlated with increased dose of NSCs [41]. However, clinical trials were performed in the subacute phase and reported that the single cell dose not sufficient to improve the functional outcome (Table 1).…”
Section: Neural Progenitor Cell Therapy In the Post-acute Phase Of Stmentioning
confidence: 99%
“…However, this study is limited by small sample size and heterogeneous group. Some clinical trials are carrying at the moment in order to test first trial to explore efficacy of different doses and delivery route of stem cells in stroke [41,43]. Clinical trials that reported an improved clinical outcome after stem cell therapy are summarized in Table 2.…”
Section: Neural Progenitor Cell Therapy In the Post-acute Phase Of Stmentioning
confidence: 99%
See 1 more Smart Citation
“…16 To date, there are numerous published reports of early phase clinical trials using different types of stem cell therapy for stroke. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The majority used autologous precursor cells from the bone marrow with remainder using allogeneic neural and umbilicalderived stem cells.…”
Section: Introduction and Rationalementioning
confidence: 99%